Comparative and Integrative Approach of Conventional and Islamic Economic Theories in Islamic Economic Law Development - Jefik Zulfikar Hafizd; Yadi Janwari; Dedah Jubaedah (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
Conventional economic theory, which began with Adam Smith's seminal work on the free market and the 'invisible hand,' evolved through the contributions of Keynesianism and monetarism, focusing on government intervention and money supply control, respectively. In contrast, Islamic economic thought is deeply rooted in the Qur'an and Sunnah, with early Islamic scholars like Ibn Khaldun emphasizing justice, balance, and social welfare as core economic principles. After a period of dormancy, Islamic economics was revived in the 20th century, presenting an alternative that integrates moral and ethical values within the economic system. This research examines the integration of conventional and Islamic economic principles, particularly their role in the development of Islamic law (Sharia) and its economic applications. By adopting a comparative and integrative approach, the study analyzes both systems' concepts, principles, and practices, relying on data from books, journals, articles, and other scholarly references. The findings highlight both the similarities and differences between conventional and Islamic economics and identify complementary elements that facilitate the creation of a more just and sustainable hybrid economic model. Integrating core Islamic economic values, such as the prohibition of usury (riba) and wealth redistribution (zakat), with conventional economic frameworks can promote a more equitable and sustainable economic system. This research concludes that the synthesis of conventional and Islamic economics, underpinned by Sharia principles, can lead to the development of a more efficient, ethical, and socially just economic model..Keywords: Conventional Economics; Islamic Economics; Comparison; Economic Integration; Economic Sustainability